Beyond Linguistic Documentation: Between the National Language and Local Languages in Indonesia - Hanafi Hanafi (English Department, Faculty of Humanities, Andalas University, 2022)
This paper discusses the politics of national language policy, especially in Indonesia and the effects of the policy toward the continuity of language diversity in Indonesia. Firstly, a short review of studies in endangered languages is presented in order to fit this discussion in appropriate place in the literature. To get more specific, the Indonesian language policy and its influence toward the country’s linguistic diversity is reviewed which is followed by the description of the media’s influence upon the threat posed to the marginal local languages. After this point, Indonesian linguists’ work will be reviewed in relation to their own status as members of different communities of practice. At the end, recommendations for improving the future linguistic works are suggested in light of language documentation, preservation, and maintenance.